Association of health literacy and medication self-efficacy with medication adherence and diabetes control - Huang YM; Shiyanbola OO; Smith PD (Patient Preference and Adherence, 2018)
Yen-Ming Huang,1 Olayinka O Shiyanbola,1 Paul D Smith2 1Division of Social and Administrative Sciences, School of Pharmacy, University of Wisconsin-Madison, Madison, WI, USA; 2Department of Family Medicine and Community Health, University of Wisconsin-Madison, Madison, WI, USA Introduction: The exact pathway linking health literacy, self-efficacy, medication adherence, and glycemic control for type 2 diabetes remains unclear. Understanding the relationship between patient factors, medication adherence, and lower glycated hemoglobin (HbA1c) may help patients better manage their disease. This study examined the association of health literacy and medication self-efficacy with self-reported diabetes medication adherence, and the association of health literacy, medication self-efficacy, and self-reported diabetes medication adherence with HbA1c of patients with type 2 diabetes.Methods: This cross-sectional study utilized a face-to-face questionnaire at two family medicine clinics in a Midwestern state among 174 patients; subjects enrolled were at least 20 years old with diagnosed type 2 diabetes, prescribed at least one oral diabetes medicine, and understood English. Questionnaires were administered to assess the participants’: health literacy, using the Newest Vital Sign six-item questionnaire (NVS); self-efficacy for medication use, using the 13-item Self-Efficacy for Appropriate Medication Use Scale; and self-report medication adherence, using the eight-item Morisky Medication Adherence Scale. HbA1c values were obtained from participants’ electronic medical records. Multiple linear regressions were used to explore the association of health literacy and medication self-efficacy with both medication adherence and HbA1c level after controlling for all other covariates.Results: Self-reported health status (β = 0.17, p = 0.015) and medication self-efficacy (β = 0.53, p < 0.001) were positively associated with diabetes medication adherence. Health literacy was neither associated with diabetes medication adherence (β = -0.04, p = 0.586) nor HbA1c (β = -0.06, p = 0.542). Lower diabetes medication adherence (β = -0.26, p = 0.008) and higher number of prescribed medications (β = 0.28, p = 0.009) were correlated with higher HbA1c.Conclusion: Health literacy, as measured by the NVS, does not correlate with medication adherence or glycemic control among patients with type 2 diabetes. Interventions to improve patients’ self-efficacy of medication use may improve diabetes medication adherence. Keywords: diabetes, health literacy, medication adherence, medication self-efficacy